Investigation and Quantification of Carbon Footprint in Lagos Megacity. Issue 1 (1st January 2019) - Bola-Popoola, Abimbola Gbolahan; Fakinle, Bamidele Sunday; Abosede Odunlami, Olayemi; Sonibare, Jacob Ademola; Odekanle, Ebenezer Leke
Abstract: The presence of carbon in an environment indicates the need for urgent attention on air quality control. Lagos mega city is presently experiencing developmental projects associated with carbon emission potentials, which are yet to be quantified; hence, this study identified and quantified the sources of carbon emission in the Lagos mega city and also determined the quantity of energy consumption capacity for domestic, transportation and industries. Using fuel consumption rate and activity duration, the emissions factors approach were used to determine the quantity of Carbon dioxide (CO2 ) emission from the household, vehicular operation and electric power generators in the zones. The total CO2 emission from the three major sectors was then used to establish the carbon footprint and annual global warming potential of the mega city. This study reported a CO2 (g) emission of 9.59 × 10 13 tons CO2 -e per annum for industrial area and 2.41 × 10 16 tons CO2 -e per annum for non-industrial area. The overall carbon dioxide emission for Lagos Mega City in 2015 was 2.42 × 10 16 tons CO2 -e per annum which is higher than the value of 1.6 × 10 16 tons CO2 -e per annum predicted for Lagos BRT CO2 emission, which stands at 66.1% increase from 2014 to 2015 as the reporting periods.